Fire influences reproductive outcomes by modifying flowering phenology and mate‐availability. Issue 5 (10th January 2022) - Richardson, Lea K.; Wagenius, Stuart
Summary: A recent study posited that fire in grasslands promotes persistence of plant species by improving mating opportunities and reproductive outcomes. We devised an investigation to test these predicted mechanisms in two widespread, long‐lived perennials. We expect fire to synchronize flowering, increase mating and boost seed set. We quantified individual flowering phenology and seed set of Liatris aspera and Solidago speciosa for 3 yr on a preserve in Minnesota, USA. The preserve comprises two management units burned on alternating years, allowing for comparisons between plants in burned and unburned areas within the same year, and plants in the same area across years with and without burns. Fire increased flowering synchrony and increased time between start date and peak flowering. Individuals of both species that initiated flowering later in the season had higher seed set. Fire was associated with substantially higher flowering rates and seed set in L . aspera but not S . speciosa . In L . aspera, greater synchrony was associated with increased mean seed set. Although fire affected flowering phenology in both species, reproductive success improved only in the species in which fire also synchronized among‐year flowering. Our results support the hypothesis that reproduction in some grassland species benefits from fire.